The role of regulatory T cells and genes involved in their differentiation in pathogenesis of selected inflammatory and neoplastic skin diseases. Part I: Treg properties and functions - Nedoszytko, Bogusław; Lange, Magdalena; Sokołowska-Wojdyło, Małgorzata; Renke, Joanna; Trzonkowski, Piotr; Sobjanek, Michał; Szczerkowska-Dobosz, Aneta; Niedoszytko, Marek; Górska, Aleksandra; Romantowski, Jan; Skokowski, Jarosław; Kalinowski, Leszek; et al. (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Regulatory T cells (Treg) can be divided into two types: the natural cells (tTreg), which arise in the thymus, and the induced cells (iTreg), which are produced in peripheral tissues during immune response. The most recently published studies indicate that the supervisory functions of these cells are weakened in the pathogenesis of autoimmune and neoplastic diseases of the skin. This may be a result of the domination of other immune cells in the skin, such as Th1/Th17/Th22 and Tc1 type in psoriasis and Th2 in atopic dermatitis. The excessive activity of Treg cells can lead to immunosuppression and decrease in the number of Th1 cells, which promote the development and progression of skin cancers. In the case of cutaneous T-cell lymphomas, there are suggestions that tumor progression is associated with the acquisition of the suppressor phenotype of malignant cells. There is genetic background of Treg dysfunction in skin disorders. This article describes the types and functions of Treg cells.